The Responsibilities of the Babaláwo-Ifá Priests in the Political Activities and Judicial Administration in Ancient Yorùbá Society - Lessons for Contemporary Nigeria - Samuel Kayode Olaleye; Julius Sunday Adekoya (Yoruba Studies Review)
Babaláwo (Ifá priests) are considered as the fathers of secrets/mysteries; they are initiated to be the Custodians of Ifá (an epitome of wisdom, knowledge and power) who leads other deities. Hence, they are in charge of worship, devotions and administration of ẹbọ (sacrifice) to maintain peace and order in every community. This makes a Babaláwo to occupy a strategic position and thereby plays a significant role in the political activities and administration of any community in Yorùbáland. In addition to these responsibilities, Babaláwo serve as check and balance for the kings and their subjects in ancient Yorùbá society, Babaláwo were the custodians and enforcers of ethical codes. Therefore, they ensure proper political and administration of justice so as to make the then society free from corruption, nepotism, favoritism and all sorts of social views that characterise the modern Yorùbá society. It is on this note that this paper re-examines the responsibilities of Babaláwo in the political and administration of the ancient Yorùbá society so as to draw some lessons for the present generation. Twenty Babaláwo were interviewed and their opinions were content analysed with a view of gaining insight into the political and justice administration in the ancient Yorùbá society.